Medical skin camouflage for women in prison with self-harm scars (COVER): randomised feasibility study - Gutridge, K. (The journal of forensic psychiatry & psychology, 2025)
Far more women prisoners self-harm than women in the community or men in prison. There has been little focus on the effects on prisoners of living with self-harm scars. Medical skin camouflage (MSC), designed to cover skin disfigurement, improves quality of life for people in the community with dermatological, burn, surgical or accidental scars or marks. Its use in prison for self-harm scars has not been evaluated. COVER tested the feasibility and acceptability of a wait-list control RCT of peer-delivered MSC for women prisoners with self-harm scars, at one prison. We provide evidence of feasibility to recruit, randomise and retain women in prison in an RCT design using strategies minimising attrition from transfer between prisons or release (51 recruited, 11.8% attrition). We successfully randomised women prisoners and collected outcome measures over 12 weeks from baseline. We report improvements in the primary outcome, the Warwick-Edinburgh Mental Well-Being Scale at follow-up for intervention and control groups and valuable information to inform an economic analysis. Important lessons were learnt, applicable to other research within this unique environment, about minimising attrition and successfully involving prisoners in peer-delivered interventions. Participants and staff found the intervention acceptable and suggested it improves women’s confidence and self-esteem.